Respuesta al fosforo aplicado a dos profundidades y su efecto en el rendimiento del frijol (Phaseolus vulgaris L.) - Thung, M.; Ortega, J.; Rodríguez, R. (International Center for Tropical Agriculture, 1982)
The effect of triple superphosphate (TSP), band-applied at depths of 5 and 25 cm, with 0, 66, and 131 kg P/ha, on the yield (14 percent MC) of bean var. Carioca, G 4000, and ICA-Pijao (efficient in P utilization), and Puebla 152 (inefficient) was studied at CIAT`s exptl. station in Quilichao, Colombia. P uptake, root length, and LAI were also recorded 21 days after germination and at flowering. Harvest took place at 90 days. Av. yield of var. fertilized with P at 25 cm was 1421 kg/ha and at 5 cm, 1263 kg/ha. Optimum level of TSP was 66 kg P/ha. Efficient var. such as Carioca and G 4000 gave higher yields than Puebla 152, especially without P. Higher yields were obtained due to the increase in the no. of pods/plant and the no. of seeds/plant. The no. of seeds/pod and the wt. of 100 seeds did not enhance yields. Application at 25 cm had a positive effect on yields at all rates of P. (CIAT)